Pemanfaatan Lahan Kawasan Hutan Lindung Oleh Masyarakat Hukum Adat, Masyarakat Lokal, dan Masyarakat Dari Luar Kawasan - Sri Rahayu Muh.Saleh; Abrar Saleng; Kahar Lahae (Batulis Civil Law Review, 2022)
This study aims to find out and examine how the land use of protected forest areas by the community in East Luwu Regency is used. This study uses an empirical juridical method, using a qualitative approach, on all legal principles/rules of law, both material law and how these provisions are confronted in a fact/reality that occurs in the field. The results of this study indicate that the use of protected forest areas by the community in East Luwu Regency is divided between customary law communities, local communities, and people from outside the area. There is injustice for indigenous peoples in fulfilling the quality of their economy, because they do not yet have a designated area, the existence of their customary forest is disturbed by looting and illegal logging carried out by people outside the area. Meanwhile, local communities often receive warnings when using forests because the boundaries of the areas they can use are not clear. Communities outside the area who encroach on protected forests which are unlawful acts. Community conflicts outside the area, in this case corporations, also conflict with the interests of indigenous peoples and local communities because their interests or rights are disturbed between one another.